Survey of Geoparasites Species Diversity in some Selected Dumpsites in Lapai Town, Niger State, Nigeria - Gimba, U.N.; Oluwafemi, O. J.; Idris, N.F.; Aina, O. A. (Direct Research Journal of Public Health and Environmental Technology, 2024)
The growth of human population and rapid industrialization has led to the increasing use of urban land as dumpsites, compromising their other uses. The disposal of waste on land has led to alterations in the quality and ecology of soil. The present study assessed parasites species diversity in some selected dumpsites in Lapai town. Studies were conducted for a period of Nine months, from January, 2020 to September 2020 using standard methods of parasites identification to differentiate the parasite seen. Out of 432 samples examined, 222 parasites seen were, Ascaris lumbricus (45.59%). Taenia solium (26.70%), Strongiloides stercolaris (14.86%). Gardia lambia (1.01%) Enterobius vermicularis (1.01%) Fasciola hepatical and Trichuris trichura (1.26%), Ancylostoma duodenale (3.78%) There was a significant difference ( P<0.05) in species diversity of parasites in dumpsites. Findings call for an improvement in the basic environmental and sanitary conditions, adequate waste management services and health education on personal hygiene.